Desempenho agronômico e composição química de genótipos de feijão sob inoculação com Rhizobium tropici em manejo orgânico - Tagliatella, Edipo Vinicius dos Santos (2023)
Common bean is a legume of great importance in human nutrition. Biological nitrogen fixation in common bean crops has low efficiency due to the dependence on the genotype-strain relationship with bacteria such as Rhizobium tropici, and the interaction with environmental factors. The objective of this study was to evaluate the performance of common bean cultivars inoculated with Rhizobium tropici under organic farming, aiming to select cultivars with the best agronomic performance and potential parents for improving the crop in ecological production systems. The experiment was conducted in a two-factor factorial design with randomized complete blocks desing and four replications. The factors studied were inoculation (inoculated and non-inoculated seeds with R. tropici) and cultivar (eight commercial bean cultivars from the carioca, black, and cranberry groups). The experimental units consisted of four rows, each 3 meters long, with a spacing of 0.5 meters between rows and 12 seeds per linear meter. Pelleted poultry manure and thermophosphate were used for fertilization. Phytosanitary management was carried out using neem oil and biological products according to the current legislation. The analyzed traits included: number of pods per plant (NVP), number of grains per pod (NGV), grain yield per plant (MGP), and hundred-grain weight (MCG). The mineral composition of the grains and plant shoots was determined. Additionally, the germination percentage and germination speed index (IVG) were analyzed for the seeds obtained from the respective treatments. The data obtained were subjected to analysis of variance, and when significant differences were found by the F test, mean separation was performed using the Scott-Knott test. Significant differences among cultivars were observed for inoculation only in terms of germination percentage. Regarding the chemical composition of the grains, the best results were obtained for the following cultivars: nitrogen - IPR Tangará (4.67 g 100g-1); phosphorus - SCS CHIC 61 (0.43 g 100g-1); potassium - IPR Tangará (2.05 g 100g-1); calcium - SCS-204 Predileto (0.19 g 100g-1); magnesium - SCS-204 Predileto (0.19 g 100g-1); copper - BRSMG Realce (107.9 mg kg-1); iron - SCS-206 Potência (123.6 mg kg-1), and manganese - SCS-204 Predileto (3.65 mg kg-1). For shoot composition, no significant differences were observed among cultivars for nitrogen, phosphorus, potassium, calcium, magnesium, and iron. However, the following results were obtained for the remaining nutrients, with highlights for: potassium - IPR Urutau (4.95 g 100g-1), copper - BRS Campeiro (23.42 mg kg-1), and manganese - SCS CHIC 61 (32.62 mg kg-1). Regarding yield components, the cultivar SCS-206 Potência showed the highest NVP (22.48) and MGP (19.23). For MCG, the cultivar with the highest value was BRSMG Realce (28.29), which is an andean cultivar with significantly larger grains. Regarding the germination percentage, the cultivar that presented the best results without inoculation was SCS-206 Potência. Among the inoculated cultivars, BRS Campeiro showed the best results, differing statistically from the others. The use of Rhizobium tropici inoculant did not alter the grain yield components in organic cultivation of common beans. However, the cultivars SCS204 Predileto, SCS-206 Potência, IPR Tangará, BRSMG Realce, and the SCS CHIC 61 lineage can be selected to compose a breeding block due to their superior nutritional indices and noteworthy attributes.